Dying To Be Thin: Attachment to Death in Anorexia Nervosa - Yael Latzer; Zipora Hochdorf (The Scientific World Journal)
Anorexia Nervosa (AN) usually follows a prolonged course accompanied by significant morbidity and high mortality. AN patients have been found to have elevated and attempted suicide rates, with suicide being the second most common cause of death in AN after the complications of the disorder itself. The suicide risk in AN is similar to that in major depression or conduct disorder and linked mainly to longer duration of illness, lower weight, bingeing and purging, impulsivity-related manifestations, comorbid substance abuse, and affective disorder. This paper reviews suicidal tendency and disturbed body image, death and eating disorders, and attachment and death with clinical implications related to AN.